Too Insecure to Be a Leader: The Role of Attachment in Leadership Emergence - Yang, Yang; Wang, Yongli; Lu, Hailing; Tan, Ling (Frontiers in Psychology, 2020)
The antecedents of leadership emergence have received increasing attention over the past decades. Extant work has found that traits that involve getting along with other members in social relations can help employees emerge as leaders. However, attachment has been ignored, even though it can provide a distinct relational perspective to getting along. This study investigates the relationship between attachment and leadership emergence as well as the mediating role of negative emotion and the moderating role of initiating structure in the relationship. Specifically, based on multisource data of one hundred employees and their supervisors, the results reveal that avoidant attachment and anxious attachment exert a negative impact on leadership emergence via negative emotion. Moreover, the mediating effect on the above relationship is weaker when employees are at a high initiating structure level. The findings imply that insecurely attached employees can also be leaders if they expend more effort and focus more on task completion.